2018
DOI: 10.1044/2017_ajslp-16-0168
|View full text |Cite
|
Sign up to set email alerts
|

Response Time Inconsistencies in Object and Action Naming in Anomic Aphasia

Abstract: Our preliminary results suggest that measuring RT may be useful in characterizing retrieval difficulty in anomic aphasia and that the retrieval processes in PWA, even in those who experience mild anomia, may be less efficient or different from those processes in neurologically healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
6
1
1
Order By: Relevance
“…Response time in confrontation-naming tasks has been found to be more sensitive than accuracy when it comes to detecting mild anomia (De Dios Pérez, 2017;De Dios Pérez et al, 2020;Galletta & Goral, 2018). In the present study, response times did not decrease significantly after treatment.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Response time in confrontation-naming tasks has been found to be more sensitive than accuracy when it comes to detecting mild anomia (De Dios Pérez, 2017;De Dios Pérez et al, 2020;Galletta & Goral, 2018). In the present study, response times did not decrease significantly after treatment.…”
Section: Discussioncontrasting
confidence: 43%
“…Both participants obtained high scores on confrontation-naming tasks in terms of accuracy, but both had several instances of response latency exceeding three seconds (see Table 1). Considering that response latencies above two seconds indicate word-retrieval difficulties (De Dios Pérez, 2017;De Dios Pérez et al, 2020;Galletta & Goral, 2018;Pashek & Tompkins, 2002), latencies above three seconds were considered to be signs of marked word-finding difficulties.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also explore other potential moderators that may impact treatment efficacy, such as stimulation parameters and subject demographics within the included studies. In addition, because prior evidence suggests that persons with aphasia may perform differently based on the category of the speech target they are attempting to produce, such as actions versus objects [ 54 , 57 , 58 , 59 ], we explore whether this is a relevant distinction in the NIBS literature on PPA. Finally, we examine available studies for publication bias, in order to evaluate the degree to which it may be influencing the apparent efficacy of NIBS approaches represented in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Time pressures that are naturally present in typical faceto-face communication make this process more complex and dynamic compared to language processing in isolated, decontextualized tasks such as word-reading and picturenaming (Carragher et al, 2012;Conroy et al, 2018). On various decontextualised language processing tasks, people with aphasia have shown delayed response times compared to neurologically healthy controls (e.g., Crerar, 2004, in word retrieval Galletta & Goral, 2018;Faroqi-Shah & Gehman, 2021 and lexical access and syntactic processing Love et al, 2008). Preliminary studies suggest that delays in processing speed observed in aphasia can lead to problems in the simultaneous activation of information from different domains (e.g., syntactic or lexical), required for comprehension of longer segments of speech (e.g., Conroy et al, 2018;DeDe & Salis, 2020; also described in resource-based accounts such as Avrutin, 2000;Kolk, 2006;Miyake et al, 1994).…”
Section: People With Aphasiamentioning
confidence: 99%